Evaluating intake variables for a teacher education programme: Improving student success and process efficiency. (December 2015) - MacMath, Sheryl; Salingré, Barbara
Highlights: We evaluate 6 intake variables against practicum performance. We used a mixed-methods study over three years. It is critical to align evaluation tools with programme values. Academic prep was the least predictive, work experience was the most predictive. By altering intake variables, evaluator time can be minimized and remain valid. Abstract: This paper reports on the effectiveness of intake variables used by a Canadian post-degree teacher education programme over the period of three years to select candidates for entry into the programme. Using a mixed-methods approach, comparisons were made between intake variables (GPA, written response, work experience, reference letters, academic preparation, and interviews), and post-practicum ratings completed by faculty mentors. Post-practicum ratings were gathered on 14 programme goals (e.g., classroom management, communication, professionalism, etc.). In addition, qualitative analyses of the scoring tools and focus group interviews with involved faculty were completed. Results over three years revealed variation that led to changes in variables and scoring tools. Implications for altering future intake procedures, especially in relation to procedural efficiency, are examined.